PEMBUATAN KERTAS INDIKATOR ALAMI DARI BUNGA TELANG (CLITORIA TERNATEA), KUNYIT (CURCUMA LONGA), DAN JANTUNG PISANG (MUSA ACUMINATA) - Sahiba Sahila; Khalda Khairunnisa Mulyana; Tsalis Muthia Kamila; Mitzy Balqist Dhabitah; Nahya Alya; Achmad Dzaki; Anisa Nuraini (Universitas Samudra, 2026)
The use of synthetic indicators, which may cause chemical pollution and are relatively expensive, has encouraged the development of natural indicators that are more environmentally friendly, economical, and easily accessible. This study aimed to investigate the potential of butterfly pea flower (Clitoria ternatea), turmeric (Curcuma longa), and banana bract (Musa acuminata) extracts as materials for natural indicator paper within a pH range of 1–14. The research was conducted by extracting each material using 96% ethanol with a ratio of 1:4 for 24 hours. The resulting filtrates were diluted with distilled water and used to soak filter paper for 30 minutes to produce natural indicator papers. The indicator papers were then tested in solutions with pH values ranging from 1 to 14 to evaluate their color changes, sensitivity, and working range. The results showed that butterfly pea flower exhibited the best performance with distinct color changes from red in acidic conditions, purple near neutral pH, to green and yellow in strongly alkaline conditions. Turmeric demonstrated significant color changes mainly in alkaline conditions, changing from yellow to orange and reddish-brown, making it more suitable as an indicator for alkaline solutions. Meanwhile, banana bract showed color changes with lower intensity and less contrast compared to butterfly pea flower and turmeric. Based on the findings, butterfly pea flower has strong potential as a versatile natural indicator with a wide pH range, while turmeric is more effective for detecting alkaline solutions.